An unsteady axisymmetric flow of MHD williamson nanofluid, incorporating entropy generation and radiative heat transfer effects, over a radially stretching surface - Mohammed Almakki; Hiranmoy Mondal; Sabyasachi Mondal (Discover Molecules)
Abstract This research examines the numerical study of a two-dimensional magnetohydrodynamic Williamson nanofluid flow in the presence of a magnetic field over a radially stretching surface. In this context, the fluid flow over a moving surface in the radial direction incorporates velocity slip and normal flux of the Williamson nanofluid. The impact of Magnetohydrodynamic flow on surface temperature, along with considerations of partial velocity slip, is given particular emphasis. Additionally, convective boundary conditions are included in the boundary layer fluid flow analysis, with modeling of key fluid field parameters such as concentration, temperature, and momentum of the Williamson nanofluid. The governing partial differential equations for axisymmetric flow are reduced to a set of nonlinear ordinary differential equations using appropriate similarity transformations and are mathematically solved using the Spectral Quasilinearization Method. A significant numerical study was conducted, with results compared to recent research, demonstrating its relevance to industrial applications. Moreover, key parameters such as the Weissenberg parameter, magnetic field, Eckert number, Prandtl number, thermophoresis parameter, and radiation parameter are shown to have important effects on velocity, temperature, and concentration profiles, as illustrated through various graphs. The Spectral Quasilinearization Method is employed to obtain a convergent series solution, with the influence of various parameters on the Magnetohydrodynamic Williamson nanofluid under thermal radiation depicted in the graphs. The velocity profile is to decrease 90% with an increment in the value of the Weissenberg parameter.